Low Distribution of TIM-3+ Cytotoxic Tumor-Infiltrating Lymphocytes Predicts Poor Outcomes in Gastrointestinal Stromal Tumors. (18th February 2021) - Zhuang, Chun; Ni, Bo; Zhang, Zi-Zhen; Zhao, Wen-Yi; Tu, Lin; Ma, Xin-Li; Yang, Lin-Xi; Cao, Hui; Wang, Ming
Abstract : There are multiple tumor-infiltrating lymphocytes (TILs) and relevant immune checkpoints existing in gastrointestinal stromal tumor (GIST), which provides opportunities and rationales for developing effective immunotherapies. Recent studies have suggested that checkpoint TIM-3/Gal-9 plays a pivotal role on immune response in multiple tumors, similar to the PD-1/PD-L1, emerging as a potential therapeutic target. However, their functions in GIST are unrevealed. Hence, the expression of immune checkpoints TIM-3 and Gal-9, as well as the infiltration of CD8 + T cells and NK cells, is described in 299 cases of GIST specimens. The results showed that TIM-3 and Gal-9 are mainly expressed in TILs, rarely in tumor cells. Expression levels of TIM-3 and Gal-9 significantly differ in varying risks of GIST and exert opposite distribution trends. Indicated by prognosis analysis, high TIM-3 expression of TILs was associated with improved outcome, while low expression levels of TIM-3 in combination with low amounts of CD8 + and CD56 + TILs predict extremely poor survival. The integrated analysis of TIM-3 +, CD8 +, and CD56 + TILs as one biomarker is a reliable independent predictor of prognosis. In conclusion, low densities of TIM-3 + TILs are associated with poor survival, and integrated immune biomarkers lead to superior predictors of GIST prognosis.